Ability of chitosan membrane from blood clam (Anadara granosa) shells to removal iron level (Fe) in water - Nur Rafiqa Puspita Sari; Iva Rustanti Eri; Demes Nurmayanti; Ferry Kriswandana; Narwati Narwati (Intelektual Pustaka Media Utama, 2021)
Clam shells are a food solid waste that increases and accumulates every day, causing environmental pollution. Clam shells (Anadora granosa) contain chitin. Chitin can be processed into chitosan, which effective in absorbing heavy metals. To increase absorption, chitosan modified into a membrane. The purpose of this study was to analyze the membrane's ability of chitosan waste from blood clam shells to reduce levels of iron in water. The design of this study was pure experimentation. The object of research used was iron-containing artificial water made from iron salt powder at a dose of 4.50 mg/L. Variations of Chitosan concentration to the membranes manufacture were 1%, 2%, 3%. Analysis of the data used was One Way Anova Test. Chitosan characterization analysis using XR Diffraction showed that chitosan was isolated from shells at peak angles at 17.99o and 34.04o. The highest percentage of iron reduction was given by membranes with a chitosan concentration of 3%, which have decreased of 94%. The results showed that the membrane of blood shells chitosan can reduce iron levels in water and can be an alternative material in the utilization of clamshell waste. The membrane can be applied in simple water treatment filtration systems in the community.